1998
DOI: 10.1007/s100380050070
|View full text |Cite
|
Sign up to set email alerts
|

Novel MEN1 gene mutations in familial multiple endocrine neoplasia type 1

Abstract: The recent isolation of the gene responsible for multiple endocrine neoplasia type 1 (MEN 1) has enabled direct genetic diagnosis for people with endocrine tumors and family members of affected patients. Although MEN 1 is rarely recognized in the Japanese population compared to its prevalence in Caucasians, we have previously reported a high prevalence of this disease in a limited area (Nagano Prefecture; population, 2.15 million). In this communication, we report mutations of the MEN1 gene in kindreds living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…pcDNA/HisMenin expresses menin tagged with a 35 amino acid polypeptide at its amino terminus and pcDNA/HisMenin516FS expresses tagged mutant menin. This mutation, designated either 1650insC 4) or 1657insC, 7,8) has been identified in patients with MEN 1, and causes a frame shift at amino acid 516 with a new termination codon after amino acid 530. Whole cell extracts of transfected cells were subjected to immunoblotting.…”
Section: Development Of Site-specific Anti-menin Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…pcDNA/HisMenin expresses menin tagged with a 35 amino acid polypeptide at its amino terminus and pcDNA/HisMenin516FS expresses tagged mutant menin. This mutation, designated either 1650insC 4) or 1657insC, 7,8) has been identified in patients with MEN 1, and causes a frame shift at amino acid 516 with a new termination codon after amino acid 530. Whole cell extracts of transfected cells were subjected to immunoblotting.…”
Section: Development Of Site-specific Anti-menin Antibodiesmentioning
confidence: 99%
“…2,3) Germline mutations of MEN1 have been identified in most subjects with familial and sporadic MEN 1 [2][3][4][5][6][7][8] and in some kindreds with familial hyperparathyroidism. [9][10][11] Somatic MEN1 gene mutations have also been identified in some sporadic parathyroid adenomas, 12) endocrine pancreas tumors 13) and lung carcinoid tumors.…”
mentioning
confidence: 99%
“…In the present patient, pathological evidence of primary hyperparathyroidism, which is the most commonlesion in patients with MEN 1 (22), was not obtained by autopsy. However, genetic analysis of the MEN1gene confirmed that the patient was affected with MEN 1 (12).…”
Section: Discussionmentioning
confidence: 96%
“…Direct sequencing of the MEN1gene of the patient and his son revealed a heterozygous 4 base deletion (738del4) in exon 3, which produces a truncated translation product (12). To characterize the pancreas head tumor, several examinations were performed.…”
Section: Case Reportmentioning
confidence: 99%
“…In addition to these major lesions, several others may also occur, although less frequently, in MEN 1 patients, e.g., adrenal cortical tumors, facial angiofibromas, lipomas, neuroendocrine tumors, thyroid neoplasms, pheochromocytomas, malignant melanomas, and testicular teratomas. The prevalence of MEN 1 syndrome is usually estimated as 1/30,000-1/50,000, but it may be higher in some limited areas (Sakurai et al 1998). The age of onset ranges from 6 to 81 years.…”
Section: Introductionmentioning
confidence: 99%